Laser‐Triggered Proton Acceleration From Micro‐Structured thin Targets. Issue 10 (December 2013) - Brantov, A.; Bychenkov, V. Yu.
Abstract By using relativistic massively parallel PIC code MANDOR, which features arbitrary target design including 3D micro‐structuring, a study of ion acceleration in short laser pulse interaction with different thin targets has been performed. Based on 3D simulation results it has been shown that micro‐structures on the front surface of thin plane targets increase a number and energy of hot electrons in comparison with that for the case of pure plain foils of optimal thickness. As a result, the energy of accelerated ions also increases up to 50%. However, the efficiency of ion acceleration from structured target reduces with laser pulse intensity increase, so that for laser pulses of ultra‐relativistic intensity a positive role of surface micro‐structuring diminishes. We have also studied to which extent a sub‐ps imperfection of the laser pulse shape, which smoothes the surface micro‐structures suppresses high‐energy ion generation. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)